Septic shock, hyperferritinemic syndrome, and multiple organ dysfunction without respiratory failure in a patient with disseminated histoplasmosis and advanced HIV disease - Silva, Jussemara Souza da; Ernandes, Bruno Correia; Fernandes, Carol Lee Luna; Correia, Ademir Silva; Ponce, Cesar Cilento; Sztajnbok, Jaques; Rodrigues, Camila; Vidal, José Ernesto (Revista do Instituto de Medicina Tropical de São Paulo, 2023)
No applicable